Optimal sensor placement of bridge structure based on sensitivity‐effective independence method - Wenhao Chai; Yaxun Yang; Haibo Yu; Fuli Yang; Zhikui Yang (IET Circuits, Devices and Systems, 2022)
Abstract Taking the optimal sensor placement problem in bridge structural health monitoring as the study object and relying on the engineering example of a simply supported steel truss bridge, the improved optimal sensor placement method based on sensitivity‐effective independence method was proposed. Using the sensitivity coefficient reflecting structural damage, the proposed method could modify the effective independence method reflecting the maximum linear independence. The proposed method further optimizes the sensor placement method. A method for selecting the number of models based on modal closeness was proposed and makes the selection of the number of modes more objective. The example analysis shows that evaluations using this method are effective for multiple evaluation criteria. The method ensures observability of the mode vector and identifiability of structural damage. It is an effective optimal sensor placement algorithm for the bridge structure.